TATA LAKSANA OPERASIONAL KANTOR DEPAN PADA PT. MUDARIS MANDIRI WISATA - Dewi Lismiati; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The tittle of this research is Front Office Operational Implementation at PT. Mudaris Mandiri Wisata. This Research aims to : (1) to know How the Front Office Operational Implementation at PT. Mudaris Mandiri Wisata, (2) to explain the assessment system about front office operational implementation, (3) to know the threat that happened to Front Office operational Implementation at PT. Mudaris Mandiri Wisata. This Research was used qualitative method with descriptive approach to describe and explain the condition that happened by collecting the data and information on the field. The Informant key on this research was 1 Front Office staff of PT.Mudaris Mandiri Wisata. This research was hold at PT. Mudaris Mandiri Wisata, Rambutan St, No.19 B, East Sidomulyo, Marpoyan Damai Subdistrict, Pekanbaru, Riau. This Research was hold about 4 months, start from February-May 2021. In this Research, the Collecting data technique was Observation, Intervie and Documentation. Based on the result, we can conclude that the Front Office Staff at PT.Mudaris Mandiri Wisata have done all the thing that reverse to the theory. Beside, for assessment system of Front office Operational that implemented by the Management based on 2 assessment side, that is the assessment from customers and the assessment from Company Manager, and it will be evaluated each month.Key word : Implementation, Front Office, Travel Agency